Karakteristik Klinikopatologi Adenokarsinoma Prostat di Rumah Sakit Hasan Sadikin dari Tahun 2016-2023 - Farah Farera; Anglita Yantisetiasti; Hasrayati Agustina (Majalah Patologi Indonesia, 2026)
Background Prostate adenocarcinoma (PA) ranks as the fifth most prevalent malignancy in men and the fifth leading cause of death in Indonesia. The growing number of elderly population and increased use of Prostate Specific Antigen (PSA) testing have led to a threefold rise in Prostate Carcinoma (PC) incidence in recent years. This study aims to profile the clinicopathological characteristics of PA cases at Hasan Sadikin General Hospital (RSHS) in Bandung during the period 2016-2023.   Methods We conducted a descriptive, cross-sectional study at RSHS in Bandung, utilizing medical records for data collection. Inclusion criteria comprised all histopathologically diagnosed PA cases between 2016 and 2023, with exclusion criteria pertaining to patients with incomplete medical records.   Results Our study revealed an average patient age of 72±9.0 year old. The most prevalent age group was those aged 70-79 years old (n=73, 38.8%). The mean PSA level among patients was 256±375.5 ng/ml). The majority of patients were diagnosed at stage IV (n=128, 68.1%). Biopsy was the most frequently used specimen collection method (n=154, 81.9%). Most samples exhibited a Gleason Score of 9 (n=65, 34.6%), belonged to Grade Group 5 (n=84, 44.7%), and had a poorly differentiated histopathological grade (n=132, 70.2%). Approximately 68.1% of patients presented with metastatic disease, with bone metastases being the most common (n=55,70,5 %).   Conclusion PA typically manifests in older individuals, frequently manifesting in 70-79 age group with less favorable histopathological features.